2019
DOI: 10.1101/19011049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An international multicenter examination of MOG antibody assays

Abstract: Objectives: To compare the reproducibility of 11 antibody assays for IgG and IgM myelin oligodendrocyte glycoprotein antibodies (MOG-IgG, MOG-IgM) from five international centers. Methods: The following samples were analyzed: MOG-IgG clearly positive sera (n=39), MOG-IgG low positive sera (n=39), borderline negative sera (n=13), clearly negative sera (n=40), and healthy blood donors (n=30). As technical controls, 18 replicates (9 MOG-IgG positive and 9 negative) were included. All samples and controls were re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…There are only two other cases of myelitis following SARS-CoV-2 infection associated with MOG-IgG: one case of bilateral optic neuritis and LETM, and a multifocal mid-thoracic spinal cord myelitis and HHV6 coinfection/reactivation which confounds interpretation of the clinical findings ( Jumah et al, 2020 ; Zhou et al, 2020 ). Furthermore, MOG-IgG was not determined by cell based assay in these cases, and thus laboratory significance of the finding is unknown ( Reindl et al, 2020 ; Reindl and Waters, 2019 ).…”
Section: Discussionmentioning
confidence: 94%
“…There are only two other cases of myelitis following SARS-CoV-2 infection associated with MOG-IgG: one case of bilateral optic neuritis and LETM, and a multifocal mid-thoracic spinal cord myelitis and HHV6 coinfection/reactivation which confounds interpretation of the clinical findings ( Jumah et al, 2020 ; Zhou et al, 2020 ). Furthermore, MOG-IgG was not determined by cell based assay in these cases, and thus laboratory significance of the finding is unknown ( Reindl et al, 2020 ; Reindl and Waters, 2019 ).…”
Section: Discussionmentioning
confidence: 94%
“…Few AQP4− patients with clinical characteristics of NMOSD have been identified as having detectable serum concentration of antibodies against MOG, a protein expressed on the outer surface of the myelin sheath and oligodendrocytes (Kitley et al, 2012;Mader et al, 2011;Reindl et al, 2020). Multiple clinical, histopathological, and laboratory investigations demonstrated that patients with AQP4−/MOG+ NMOSD have a different underlying pathogenesis from patients with AQP4+ NMOSD (Borisow et al, 2018;Kim et al, 2020;Marignier et al, 2013;Zamvil & Slavin, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A diagnosis of NMOSD without AQP4-IgG additionally required documented negative testing for MOG-IgG (AQP4-IgG À /MOG-IgG À NMOSD). Standard testing for AQP4-IgG and MOG-IgG was performed with cell-based assays 27,28 in the majority of the patients (at least 70% in AQP4-IgG + NMOSD and 82% in MOGAD, for the rest no documentation of assay available). Patients were excluded in case of incomplete core data sets or absence of at least one documented EDSS examination in stable disease phase without relation to an attack.…”
Section: Study Setting and Data Collectionmentioning
confidence: 99%